2016
DOI: 10.1007/s00253-016-7624-3
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-based magneto-elastic biosensors: potential devices for detection of pathogens and associated toxins

Abstract: This work describes the design and development process of an immunosensor. The creation of such devices goes through various steps, which complement each other, and choosing an efficient immobilization method that binds to a specific target is essential to achieve satisfactory diagnostic results. In this perspective, the emphasis here is on developing biosensors based on binding antigens/antibodies on particular surfaces of magneto-elastic sensors. Different aspects leading to the improvement of these sensors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 145 publications
0
14
0
Order By: Relevance
“…Both techniques achieve the ordered and orientation-specific immobilization of antibodies onto the surfaces through their constant regions (Fc) and result in their antigen recognition fragments (Fab) being aligned and facing away from the surfaces, without the need to interfere with the antibody's native structure. As neither of them directly result in the formation of a stable covalent bond between the antibody and the surfaces, an important consideration towards the fabrication of a stable immunosensor platform [49], careful adjustment of the buffer pH in the case of boronic acids, and the use of a crosslinking agent in the case of protein A/G-modified surfaces is required. The obtained results highlight the importance of the antibody's orientation and its surface density in enhancing its antigen-binding capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Both techniques achieve the ordered and orientation-specific immobilization of antibodies onto the surfaces through their constant regions (Fc) and result in their antigen recognition fragments (Fab) being aligned and facing away from the surfaces, without the need to interfere with the antibody's native structure. As neither of them directly result in the formation of a stable covalent bond between the antibody and the surfaces, an important consideration towards the fabrication of a stable immunosensor platform [49], careful adjustment of the buffer pH in the case of boronic acids, and the use of a crosslinking agent in the case of protein A/G-modified surfaces is required. The obtained results highlight the importance of the antibody's orientation and its surface density in enhancing its antigen-binding capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Muir et al 124 prepared metal coordinating polymer substrates and screened a large range of transition metals to ) to achieve oriented immobilization of native anti-adiponectin antibody on carboxyphenyl multiwalled carbon nanotubes 125 and graphene oxide-carboxymethyl cellulose hybrid. 126 Recently, Welch et al 127 employed the chromium complex, [Cr(OH) 6 ] 3À , buffered with ethylenediamine as a wet chemical modification to ten commercial microtiter plates, postproduction, to improve antibody immobilization and ELISA performance. For an anti-EGFR, x-ray photoelectron spectroscopy (XPS) analysis indicated that the chromium modified microtiter plate bound twice the amount of antibody relative to the unmodified plate, and the ELISA signal more than tripled indicating improved antibody orientation.…”
Section: Metal Affinitymentioning
confidence: 99%
“…The optimized complex (1:1 chromium perchlorate hexahydrate to ethylenediamine) was used to improve the antigen detection limits of a bovine tumor necrosis factor alpha (TNFa) ELISA by an order of magnitude relative to untreated plates. In a recent study, Welch et al 29 employed a traditionally low fouling diethylene glycol dimethyl ether plasma polymer (DGpp) as a substrate for binding [Cr(OH) 6 ] 3À with subsequent antibody immobilization. When equivalent amounts of antibody were immobilized on the DGpp and the chromium functionalized DGpp substrates, a tenfold improvement in ELISA signal intensity was observed for the chromium functionalized system indicating an oriented system.…”
Section: Metal Affinitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear there is a need for a low cost, sensitive, easy to use reagent which can be added to directly compare in vitro transcription reactions without additional purification steps. Reagentless, fluorescence biosensors have been successfully employed in such roles in various biochemical assays (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%